Estudio clínico e histoquímico de la leucemia aguda en cavidad bucal - Romero M., Roberto (2001)
It was studied 15 cases; average age predominated between 7 to Iº years. The location of sharp Ieukemia was greater in gingival region 7 cases, 46.65 per cent. In the characteristic injury predominated gingival bleeding 9 cases, 60 per cent. In the histochemical study, it was determined different types of sharp leukemia according to the characteristics of blastic cells. The type of sharp linfoblastic leukemia predominated the most 8 cases, 53.3 per cent.